DISCOURSE ANALYSIS THE USE OF FORMAL AND INFORMAL LANGUAGE IN SOCIAL MEDIA - Murni Mahmud; Muftihaturrahmah Burhamzah; Mutiara Mutiara (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2026)
This study explores the use of formal and informal language in social media, specifically examining Instagram posts by Arini Nurwijayanti, an influencer based in Makassar, Indonesia. The research employs a qualitative approach, utilizing discourse analysis to understand the linguistic features present in her social media interactions. Data was collected from Arini Nurwijayanti's Instagram account (@arininurwijayanti), focusing on textual data from her posts. The collected data was then analyzed using a discourse analysis framework, examining syntax and sentence structure, the use of abbreviations, slang, emojis, and hashtags, as well as the degree of grammatical correctness. The findings reveal a dominant use of informal language in Arini's posts, characterized by simple sentence structures, colloquial vocabulary (e.g., "mau belanja," "udah abis"), and code-mixing (e.g., "skip dulu"). This informal style fosters a sense of relatability and engagement with her audience. While effective for building rapport, the analysis also indicates deviations from formal grammar, including fragmented sentences and a lack of punctuation. The study suggests that Arini Nurwijayanti strategically employs informal language to create a casual and approachable persona, thereby enhancing her connection with followers. The research highlights the importance of understanding the interplay between language, audience, and platform in shaping digital communication strategies. The study also implies that formal and informal language usage impacts different assumptions that can be made by a social media user.Keywords: social media, discourse analysis, language